(untitled) (Bangladesh Medical Journal Khulna, 2012)
Percutaneous ethanol injection (PEI) has been most widely performed as one of the effective ablative techniques for small Hepatocellular carcinoma (HCC). The ideal patient for alcohol injection should have fewer than three HCC tumors, each of which is well defined, less than 3cm in diameter, surrounded by a fibrous shell and not near the surface of the liver. It is contraindicated in patients with gross ascites, uncorrectable coagulopathy, obstructive jaundice and main portal vein thrombosis. This procedure is performed under ultrasound guidance in an outpatient basis with a 21-22 G needle & 95-100 % alcohol. Ethanol causes dehydration and subsequent necrosis of the HCC. Depending upon the tumor size, 2 - 12 ml ethanol per lesion is given, the numbers of session, generally, are once or twice per week for four to six sessions. Adverse effects are pain, fever, a feeling of alcohol intoxication and elevated transaminase. A major problem of PEI is tumor recurrence. Follow-up is done by imaging, tumor marker assay and selective use of fine-needle aspiration and biology. Several studies have shown similar or even better results with PEI than with surgical resection. PEI should be considered as first line treatment option for small HCC for its ease of execution, safety, low cost, repeatability & therapeutic efficacy. DOI: http://dx.doi.org/10.3329/bmjk.v43i1-2.13017 Bang Med J (Khulna) 2010; 43: 12-17